Quality of antenatal and childbirth care in selected rural health facilities in Burkina Faso, Ghana and Tanzania: similar finding - Duysburgh, Els; Zhang, W.-H.; Ye, M.; Williams, A.; Massawe, S.; Sié, A.; Williams, J.; Mpembeni, R.; Loukanova, Svetla; Temmerman, M. (Tropical medicine & international health, 2013)
Objectives To measure pre-intervention quality of routine antenatal and childbirth care in rural districts of Burkina Faso, Ghana and Tanzania and to identify shortcomings. Methods In each country, we selected two adjoining rural districts. Within each district, we randomly sampled 6 primary healthcare facilities. Quality of care was assessed through health facility surveys, direct observation of antenatal and childbirth care, exit interviews and review of patient records. Results By and large, quality of antenatal and childbirth care in the six districts was satisfactory, but we did identify some critical gaps common to the study sites in all three countries. Counselling and health education practices are poor; laboratory investigations are often not performed; examination and monitoring of mother and newborn during childbirth are inadequate; partographs are not used. Equipment required to provide assisted vaginal deliveries (vacuum extractor or forceps) was absent in all surveyed facilities. Conclusion Quality of care in the three study sites can be improved with the available human resources and without major investments. This improvement could reduce maternal and neonatal mortality and morbidity.
Gesehen am 05.01.2021